National players vs. foreign players: what distinguishes their game performances? A study in the Portuguese Basketball League - Guimarães, E.; Santos, A.; Santos, E.; Tavares, F.; Janeira, M. A. (Revista Internacional de Ciencias del Deporte, 2018)
This study identified the game-related statistics that best differentiate national and foreign players competing in the 2014/15 and 2015/16 Portuguese Basketball League (LPB) seasons. Sample included 337 male professional basketball players, divided in national (n=249), community (n=30) and extra-community (n=58) according to their nationality. The following seventeen game-related statistics were obtained from the official box-scores of the Portuguese Basketball Federation: minutes, points scored, 2-point shots made, 2-point shots attempt, 3-point shots made, 3-point shots attempt, free throws made, free throws attempt, defensive rebounds, offensive rebounds, assists, turnovers, steals, blocks, fouls committed, fouls received and MVP. When controlling for playing time, foreign players outperformed national players in almost all offensive and defensive tasks of the game. Nevertheless, national players presented better performances in 3-point shots attempt (p<0.05, 2=0.02), assists (p<0.01, 2=0.04) and steals (p<0.01, 2=0.03). Despite the supremacy of foreign players, it is acceptable to suggest that the high effectiveness demonstrated by the domestic players in these tasks of the game make them also essential for teams` success.